Countering Avoidance Strategies Used by Fishers to Avoid Detection During Illegal Fishing - Arias, Adrian; Bergseth, Brock J.; Weekers, Damian; Wilcox, Chris (Frontiers in Marine Science, 2021)
• Noncompliers typically avoid detection by authorities, benefitting from increased catch and income. While detection-avoidance strategies (e.g., secret compartments to hide illegal catch) are commonly used in the nature conservation context, they remain largely unstudied. • We address this knowledge gap in three sections. First, we introduce and hypothesise the likelihood of noncompliers adopting detection-avoidance strategies in the broader conservation context. Second, we identify and categorise detection-avoidance strategies used by small-scale fishers. Third, we provide recommendations for countering detection-avoidance strategies (i.e., countermeasures). • Because countermeasures are context-specific, they should be informed through systematic processes such as the intelligence cycle. If used properly, enforcement activities and countermeasures can help build voluntary compliance, particularly through procedural justice, or acting in a way that users perceive as fair and just.